WORKLOAD ANALYSIS USING THE FULL TIME EQUIVALENT (FTE) METHOD TO OPTIMIZE THE WORKFORCE OF THE LEGAL SETTLEMENT UNIT AND ITS SUPPORTING UNIT PT TELKOM INDONESIA (PERSERO) TBK. - Deri Apriadi (SEAN Institute, 2022)
PT. Telekom Indonesia (Persero), Tbk or referred to as Telkom is the only State-Owned Enterprise (BUMN) engaged in telecommunications in providing telecommunications services with the largest network in Indonesia. At PT Telkom there is a legal settlement unit where this unit is engaged in the settlement or legal disputes, these problems can be resolved with the assistance of the State Attorney (JPN). In the legal settlement unit there are human workers to help realize the company's goals. This study does not use quantitative and qualitative methods and does not test hypotheses, but only describes and analyzes data, the purpose of this study is to find out how the workload of the legal settlement unit and its supporting units is and to determine the optimal number of workers at PT Telkom Indonesia (Persero). ), Tbk. This study uses the Full Time Equivalent (FTE) method, a workload analysis method that measures the length of time for completion of work. Based on the results of research using the FTE method, it is known that there is an imbalance in the workload of 8 units. Where there are 6 units with excessive workloads including the Legal settlement unit, 3 proposed workers are needed, Telkom regional 3 needed 7 proposed workers, Telkom regional 4 needed 4 workers, Telkom regional 5 needed 3 proposed workers, Telkom regional 6 needed 2 workers proposed work, and telkom regional 7 required 2 proposed workers, while only 2 units had a normal (fit) workload, namely regional telkom 1 and 2. The result is that the total workload on all units can be carried out by 42 workers. And then the workload balance value is greatly increased from the previous 5% to 80%.